Life strategy of Antarctic silverfish promote large carbon export in Terra Nova Bay, Ross Sea - Clara Manno; Erica Carlig; Pier Paolo Falco; Pasquale Castagno; Giorgio Budillon (Communications Biology, 2024)
Abstract Antarctic silverfish Pleuragramma antarcticum is the most abundant pelagic fish in the High Antarctic shelf waters of the Southern Ocean, where it plays a pivotal role in the trophic web as the major link between lower and higher trophic levels. Despite the ecological importance of this species, knowledge about its role in the biogeochemical cycle is poor. We determine the seasonal contribution of Antarctic silverfish to carbon flux in terms of faeces and eggs, from samples collected in the Ross Sea. We find that eggs and faeces production generate a flux accounting for 41% of annual POC flux and that the variability of this flux is modulated by spawning strategy. This study shows the important role of this organism as a vector for carbon flux. Since Antarctic silverfish are strongly dependent on sea-ice, they might be especially sensitive to climatic changes. Our results suggest that a potential decrease in the biomass of this organism is likely to impact marine biogeochemical cycles, and this should be factored in when assessing Southern Ocean carbon budget.